2000
DOI: 10.1073/pnas.97.22.11759
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of sound amplification in the mammalian cochlea

Abstract: Mammalian hearing depends on the enhanced mechanical properties of the basilar membrane within the cochlear duct. The enhancement arises through the action of outer hair cells that act like force generators within the organ of Corti. Simple considerations show that underlying mechanism of somatic motility depends on local area changes within the lateral membrane of the cell. The molecular basis for this phenomenon is a dense array of particles that are inserted into the basolateral membrane and that are capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…To test for the presence of this protein in isolated cells OHCs, glucose in the external solution was isosmotically replaced with fructose. OHCs reversibly shortened, compatible with the proposal that water was moving into the cells along with transported fructose (15,111). The uptake was compatible with transport with a Michaelis constant K m of 16 mM and comparable to that found for the fructose transporter GLUT5 in other systems.…”
Section: Sugar Transportsupporting
confidence: 73%
“…To test for the presence of this protein in isolated cells OHCs, glucose in the external solution was isosmotically replaced with fructose. OHCs reversibly shortened, compatible with the proposal that water was moving into the cells along with transported fructose (15,111). The uptake was compatible with transport with a Michaelis constant K m of 16 mM and comparable to that found for the fructose transporter GLUT5 in other systems.…”
Section: Sugar Transportsupporting
confidence: 73%
“…Two mechanisms have been suggested. First, outer hair cell electromotility, which involves cell body contractions (9), could be an important element of the amplifier in the mammalian cochlea (10)(11)(12). Second, the hair bundle, which is the mechanosensitive organelle at the apical surface of the hair cell, could generate forces and movements that contribute to amplification (13)(14)(15).…”
mentioning
confidence: 99%
“…The outer hair cells (OHCs) are instrumental in the active behaviour of the biological cochlea [2]. Many researchers have shown that the OHCs poise themselves on or close to a dynamical nonlinearity known as a Hopf bifurcation and that this is the source of the nonlinear amplification observed in the biological cochlea ( [3], [4], [5] and [6]).…”
Section: Introductionmentioning
confidence: 99%